Ikaros Proteins in Tumor: Current Perspectives and New Developments - Xia, Ruolan; Cheng, Yuan; Han, Xuejiao; Wei, Yuquan; Wei, Xiawei (Frontiers in Molecular Biosciences, 2021)
Ikaros is a zinc finger transcription factor (TF) of the Krüppel family member, which significantly regulates normal lymphopoiesis and tumorigenesis. Ikaros can directly initiate or suppress tumor suppressors or oncogenes, consequently regulating the survival and proliferation of cancer cells. Over recent decades, a series of studies have been devoted to exploring and clarifying the relationship between Ikaros and associated tumors. Therapeutic strategies targeting Ikaros have shown promising therapeutic effects in both pre-clinical and clinical trials. Nevertheless, the increasingly prominent problem of drug resistance targeted to Ikaros and its analog is gradually appearing in our field of vision. This article reviews the role of the Ikaros in tumorigenesis, the mechanism of drug resistance, the progress of targeting the Ikaros in both pre-clinical and clinical trials, and the potential use of associated therapy in cancer therapy.